2021
DOI: 10.1097/md.0000000000027033
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture treatment on attention deficit hyperactivity disorder

Abstract: Background: Attention Deficit Hyperactivity Disorder (ADHD) is the most common behavioral disorder in childhood. Acupuncture treatment of ADHD has formed a relatively systematic theoretical and clinical treatment system which achieved satisfactory results. However, there has been no systematic evaluation of its effectiveness and safety. The purpose of this study was to evaluate the efficacy and safety of acupuncture in the treatment of ADHD. Methods: A systematic search… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Another, similar review identified nine main channels that contribute to autism symptoms [ 35 ]. The increasing number of protocol-type articles shows that research designs in this field have become more rigorous and scientific, consistent with the rapid development of evidence-based medicine in recent years [ [36] , [37] , [38] , [39] ].…”
Section: Discussionmentioning
confidence: 93%
“…Another, similar review identified nine main channels that contribute to autism symptoms [ 35 ]. The increasing number of protocol-type articles shows that research designs in this field have become more rigorous and scientific, consistent with the rapid development of evidence-based medicine in recent years [ [36] , [37] , [38] , [39] ].…”
Section: Discussionmentioning
confidence: 93%